Zur Struktur der Ratschläge im Deutschen und Polnischen - Prokop, Izabela (Wydawnictwo Naukowe UAM, 1991)
Advice is some of the most frequently used acts of speech both in written and spoken language. Their boundaries are flexible and their structure is very much differentiated. This article is an attempt at listing some of the linguistic realizations of this speech act which occur in journals in Polish and in German. In the further part of the article the author introduced a differentiation between institutionalized and private advice and analysed the former kind.